Motor control and skill acquisition in pediatric physical therapy: an enactive proposal - Sørvoll, Marit; Øberg, Gunn Kristin; Girolami, Gay L. (Frontiers in Psychology, 2023)
Theories of motor control and skill acquisition strongly influence and guide various fields of clinical practice. In last decades, changes in theoretical frameworks related to the conceptualization of brain plasticity, functional structures within the child, and environment have led to a revision of therapy approaches progressing from therapist-driven to child-initiated approaches. Even though theoretical frameworks and clinical practice are closely linked to the child`s body, the profession has paid less attention to theories concerning the body`s role and status in interpersonal relationships when fostering motor control and skill acquisition in children.In this theoretical paper we discuss the theoretical frameworks of motor control and skill acquisition that currently guide clinical practice. Through highlighting valuable contributions of these theories, we explore theoretical and practical benefits pediatric physical therapy can acquire by taking an enactive approach as a means to bring the child as a subject into focus. We rely on enactive concepts of embodiment, autonomy, and participatory sense-making in our exploration to provide an extended understanding of motor control and skill acquisition shaping our beliefs about what counts in therapeutic encounters in pediatric physical therapy.